Home-based nursing interventions improve knowledge of disease and management in patients with heart failure - Karina de Oliveira Azzolin; Dayanna Machado Lemos; Amália de Fátima Lucena; Eneida Rejane Rabelo-Silva (Universidade de São Paulo, 2015)
OBJECTIVE: to assess patient knowledge of heart failure by home-based measurement of two NOC Nursing Outcomes over a six-month period and correlate mean outcome indicator scores with mean scores of a heart failure Knowledge Questionnaire.METHODS: in this before-and-after study, patients with heart failure received four home visits over a six-month period after hospital discharge. At each home visit, nursing interventions were implemented, NOC outcomes were assessed, and the Knowledge Questionnaire was administered.RESULTS: overall, 23 patients received home visits. Mean indicator scores for the outcome Knowledge: Medication were 2.27±0.14 at home visit 1 and 3.55±0.16 at home visit 4 (P<0.001); and, for the outcome Knowledge: Treatment Regimen, 2.33±0.13 at home visit 1 and 3.59±0.14 at home visit 4 (P<0.001). The correlation between the Knowledge Questionnaire and the Nursing Outcomes Classification scores was strong at home visit 1 (r=0.7, P<0.01), but weak and non significant at visit 4.CONCLUSION: the results show improved patient knowledge of heart failure and a strong correlation between Nursing Outcomes Classification indicator scores and Knowledge Questionnaire scores. The NOC Nursing Outcomes proved effective as knowledge assessment measures when compared with the validated instrument.